BUILDING BRAND TRUST IN THE MEDIA CONVERGENCE ERA (TOURISM OFFICE OF PT HIS TOUR AND TRAVEL BALI) - Ardianti, Anggita; Isnaini, Santi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze brand trust in the era of media convergence at the tourism office of PT His Tour And Travel Bali. Research using qualitative research methods is descriptive, because the interview technique. Data analysis techniques include data reduction, data display and conclusion of brand characteristics, and company characteristics are used as measuring tools in building brand trust. The results of this study indicate that the characteristics and company characteristics in building a brand truss at PT His Tour And Travel Bali have a good impact on the company, therefore PT His Tour and Travel Bali must continue to increase brand trust by paying attention to brand characteristics and company characteristics that have a positive impact on the company. Keywords: Brand Trust, Convergence Era, Media, PT His Tour And Travel Bali